Competitive strategies in fashion industries: portuguese footwear industry - Marques, António Manuel Dinis Ribeiro (2017)
Portugal is an important player in the European fashion industry. The Portuguese footwear industry, “low-tech” and traditional industry, dominated by SMEs and located in two main clusters, is a success case in the Portuguese economy. After a long period of decline until 2009, the footwear companies prepared new strategies that made big changes in the image and performance achieved. Since 2009, exports have increased more than 55% and the Portuguese footwear has grown in almost all the most important foreign markets. The competitive strategies followed by the Portuguese footwear companies are different and they can be clearly identified according Porter’s three generic competitive strategies: cost leadership, differentiation and focus strategy. This paper had analysed seven Portuguese footwear companies (seven cases, case study strategy) and the results obtained shows how important is to have the right approach to the markets, according the internal and external resources that each firm has available. The footwear clusters in Portugal and the sectorial organizations are also very important in this competitive performance achieved by the companies. Last years the Portuguese government recognize this increasing importance of the fashion industries and prepared several programs to promote these industries in Europe and other continents.